SWOT ANALYSIS IN THE PROVISION OF ECONOMIC SECURITY OF AGRARIAN ENTERPRISE - Bondarchuk, N.V. (The actual problems of regional economy development, 2019)
The article is directed at exploring the technology of conducting SWOT-analysis in agricultural enterprise in order to ensure its economic security. SWOT-analysis is of particular importance. SWOT - analysis is a tool of strategic management which can used in the conditions of aggravation of competition, violation of financial stability, uncertainty in the market. The general aim of the article is investigate and identifyy the internal and external outsiders of the agricultural enterprise via SWOT-analysis to ensure its effective management. The research used general scientific methods, systematic and complex analysis. The article states that the assessment of the level of economic security of agrarian enterprise is formed in the context of such basic functional components, such as: financial, innovative, personnel, technical and technological. Each of these components is evaluated by a system of qualitative and quantitative components, which include an integrated assessment of the level of economic security with the study of their important indicators. Algorithm for conducting a SWOT-analysis for agrarian enterprise is proposed, which consistssuch steps: 1) identification of important factors that influence on the enterprise activity; 2) identifying the enterprise’s opportunities and threats; 3) grouping of opportunities and threats by certain interconnection; 4) building a complex matrix and formulating a strategy. It is established that the application of this strategic management tool allows to identify timely along with the company's strengths and opportunities existing threats and weaknesses, to build an effective strategy of the enterprise activity and at the expense of the strengths and opportunities of the enterprise to retain its share in the market, improve financial position, achieve benefits in front of competitors, increase production volumes.